Internet Safety and Malaysian Students: A Study of Female Undergraduates and Their Net Pals - Cheong Lee Mei, Dianne (UiTM Publisher, 2007)
Malaysian female undergraduates are perceived as able to rationally evaluate and estimate risks towards Net pals. Friendship is secured online while deception and fraud are revealed offline. Based on what they have been informed, the female undergraduates may know their Net pals' likes and dislikes but the invisible cyber veil does not allow them to penetrate the illusion and accurately evaluate a person's character and personality. This study examined how Malaysian female undergraduates use the Internet, perceive risks in meeting Net pals and the safety awareness surrounding cyber friendship. Responses of 118 female undergraduates (43% from UiTM, 30% from UM, 27% from MMU) to a survey indicated that Net pals were befriended through chat rooms and websites. More than half of the female undergraduates would have a face-to-face meeting with their Net pals without the knowledge of relevant parties and have done at least one potentially unsafe behaviour. If the extent and level of Internet safety awareness is known, the problem of Internet deception that might lead to potential social problems such as rape and sexual abuse can be effectively addressed.